2022
DOI: 10.18502/ijph.v51i9.10555
|View full text |Cite
|
Sign up to set email alerts
|

Happiness Levels and Leisure Life Satisfaction for Sports Leisure Activities Participation: Implication for Physical Education in Korea

Abstract: Background: The study aimed to analyze happiness levels and leisure life satisfaction related to participation in sports leisure activities, and the differences in satisfaction levels by the type of participation events and participants’ demographic backgrounds. Methods: This study was based on the 2020 Korea National Leisure Activities Survey using stratified multi-stage cluster sampling with a population over the age of 15 years and a nationwide survey. Moreover, a household visit interview survey was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…While there was no significant difference between male and female groups, it was found that attitude towards leisure had a strong effect on the level of satisfaction and happiness in leisure activities. Bae (2022) conducted a study on the happiness levels and leisure life satisfaction levels of individuals for participation in sports and leisure activities and stated that there was no significant difference between gender variables and leisure satisfaction. Contrary to these results, some studies disagree with our study.…”
Section: Discussionmentioning
confidence: 99%
“…While there was no significant difference between male and female groups, it was found that attitude towards leisure had a strong effect on the level of satisfaction and happiness in leisure activities. Bae (2022) conducted a study on the happiness levels and leisure life satisfaction levels of individuals for participation in sports and leisure activities and stated that there was no significant difference between gender variables and leisure satisfaction. Contrary to these results, some studies disagree with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Kim, Heo, Dvorak, Ryu and Han (2018) cite research findings according to which life satisfaction is significantly related to outdoor activities, physical activities, activities carried out at home and social activities. Bae (2022) reports that participants in leisure sport activities tend to exhibit a higher level of happiness and satisfaction in comparison with those who participate in leisure time activities which do not involve sports. Zhang, He and Chen (2020) also point out the relationship between doing sports and life satisfaction.…”
Section: Analysis Of Leisure Activities As a Predictors Of Life Satis...mentioning
confidence: 99%
“…Studies examining the effect of marriage on fitness engagement have produced mixed results. Alexandris and Carroll ( 36 ), Lee and Bhargava ( 37 ), and Bae ( 38 ) found varying outcomes in their investigations. However, a longitudinal study spanning from 1987 to 2005, which involved 8,871 adults, revealed that transitioning from singlehood to marriage was associated with an increase in fitness among women, while divorce and remarriage were linked to an increase in fitness among men ( 10 ).…”
Section: Introductionmentioning
confidence: 98%